2018
DOI: 10.1038/s41598-018-28527-2
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Structure-Function Design Principle Underlies Efficient Signaling Dynamics in Neurons

Abstract: Dynamic signaling on branching axons is critical for rapid and efficient communication between neurons in the brain. Efficient signaling in axon arbors depends on a trade-off between the time it takes action potentials to reach synaptic terminals (temporal cost) and the amount of cellular material associated with the wiring path length of the neuron’s morphology (material cost). However, where the balance between structural and dynamical considerations for achieving signaling efficiency is, and the design prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…While physiologically many variables contribute to neuronal delays, a rough indication of the delay in synaptically connected cortical neurons was estimated to be 6-14 ms (Gonzalez-Burgos, 2000). We estimated similar conduction velocities and latency values in a previous study performed on basket and pyramidal neurons from the rat neocortex (Puppo et al, 2018). Given that monolayer networks of hiPSC-derived neurons may have temporal properties that differ from those observed in intact brain networks, we decided to avoid neglecting correlations that could negatively bias the inference performance by considering a larger temporal window (−22, 22) ms.…”
Section: Connectivity Analysis In Hipsc-derived Culturesmentioning
confidence: 75%
“…While physiologically many variables contribute to neuronal delays, a rough indication of the delay in synaptically connected cortical neurons was estimated to be 6-14 ms (Gonzalez-Burgos, 2000). We estimated similar conduction velocities and latency values in a previous study performed on basket and pyramidal neurons from the rat neocortex (Puppo et al, 2018). Given that monolayer networks of hiPSC-derived neurons may have temporal properties that differ from those observed in intact brain networks, we decided to avoid neglecting correlations that could negatively bias the inference performance by considering a larger temporal window (−22, 22) ms.…”
Section: Connectivity Analysis In Hipsc-derived Culturesmentioning
confidence: 75%
“…While physiologically many variables contribute to neuronal delays, a rough indication of the delay in synaptically connected cortical neurons was estimated to be 6 -14 ms [20]. We estimated similar conduction velocities and latency values in a previous study performed on basket and pyramidal neurons from the rat neocortex [50]. Given that monolayer networks of human iPSC-derived neurons may have temporal properties that differ from those observed in intact brain networks, we decided to avoid neglecting correlations that could negatively bias the inference performance We used a graph-based connectivity analysis to estimate developing connections between neurons.…”
Section: Connectivity Analysis In Hipsc-derived Culturesmentioning
confidence: 75%
“…Importantly, spatio-temporal information is implicitly contained in the estimated connectivity and delay map too; we expect therefore that, when used in combination with novel computational methodologies [66,58,67], our method will help reveal more fundamental network properties crucial to the understanding of the relationships between network topology, dynamic signaling and network functions in healthy and disease models.…”
Section: Discussionmentioning
confidence: 99%
“…Using high resolution morphological reconstructions of axon shapes, we recently showed that the refraction ratio reflects a design principle that biological neurons optimize. It reflects a balance between the wiring lengths of axons (material cellular costs) versus signaling speeds (temporal costs) [12].…”
Section: Introductionmentioning
confidence: 99%